Towards determining the age of the Camas Prairie Ripples, NW Montana: an exercise of optically stimulated luminescence (OSL) on quartz grains - Thornton, Quillen (My University, 2026)
The Camas Prairie Ripples located in northwestern Montana were originally hypothesized by Joseph Pardee in 1942 to be the result of glacial outburst flooding from Glacial Lake Missoula. Despite the chronology of flood deposits in the Channeled Scablands being well studied, the Camas Prairie Ripples, which have been previously classified based on their morphology as dune and antidune structures, have little information on the exact timing for the formation of these impressive landforms. Questions also remain as to whether these features formed in one catastrophic event or resulted from repeated ice dam failures. In this study, samples of sediment matrices within giant current ripples were collected from two different localities at varying stratigraphic depth in the Camas Prairie Basin. They were analyzed using optically stimulated luminescence on small aliquots of quartz minerals to determine the age of deposition for these features and potentially answer how many flooding events may have caused these features. It was found that ages of minerals from these features ranged from approximately 3 to 6.7 ka, which are severely underestimated potentially due to malign quartz characteristics, underlying bedrock, statistical models employed, or sampling strategy and field observation methods used in this study. However, if all ages were shifted to underestimated values equally, then there could be potential evidence for at least two separate flooding events recorded in these localities. Further use of Quaternary dating methods like optically stimulated luminescence analyses on feldspars, rock surface luminescence, and 10Be/26Al cosmogenic nuclide dating may be able to help provide more accurate ages. Examination of all this information is critical to understanding the glacial history of this region and the greater Channeled Scablands.
Keywords: Luminescence; Glacial Lake Missoula; Outburst Floods; Geology; Geomorphology; Channeled Scablands